A first-principles theoretical study on the potential thermoelectric properties of MgH2 and CaH2. (8th February 2019) - Wang, Yunxia; Ohishi, Yuji; Kurosaki, Ken; Muta, Hiroaki
Abstract: First-principles calculations, Boltzmann transport equations, and a modified Slack's model were used to investigate the Seebeck coefficient S, electrical conductivity σ, and thermal conductivity κ of hydrides MgH2 and CaH2 . As a result, a largest zT value around 0.38 and 0.55 at 1000 K could be achieved when carrier concentratio n n ∼  1.7 × 10 21 cm −3 a n d n ∼  7.4 × 10 20 cm −3 in the p -type MgH2 and CaH2, respectively. Higher zT values (>1) could be achieved by reduction of the high thermal conductivity. The results of our study gave a support that hydrides MgH2 and CaH2 could be promising as thermoelectric materials.